THE ROLE OF NEOPTERIN AS A NOVEL BIOMARKER FOR REDUCED KIDNEY FUNCTION: A COMMUNITY BASED STUDY - Widiana, G Raka; Suwitra, K; Effendi, Imam (journal of internal medicine; Vol. 12, No. 2 Mei 2011)
Cardiovascular disease is a major complication for patents with reduced kidney function. Neopterin is well known as a biomarker for cardiovascular disease, however it is not clear whether it is associated with reduced kidney function. Study was carried out in a Legian Kuta village a tourist town in Bali. Samples were underwent a series of interview, physical examination and were taken blood samples for neoperin and creatinine tests. Neoptein concentrations were tested for its normal distribution and associated with C-G formula for estimated glomerular filtration rate. Cut-off value for prediction of reduced renal function was rested using ROC curve, and calculated for sensitivity, specificity. Seventy nine samples were selected through cluster random sampling from 284 residents (177 males and 107 females) with age 46 ± 10 years, body weight 67 ± 13 kg and height 162 ± 9 cm. It was shown that neopterin concentration was normally distributed (K-S Z = 1.175, p = 0.126), with mean 6.66 ± 3.35 ng/ml and e-GFR was 89 ± 25 ml/mnt. There was significant negatively correlation between neopterin concentrations and e-GFR (R = -0.26, Rsq = 0.068, p = 0.021), using regression equation it was revealed that every 1 unit increased of neopterin concentrations produce 1.42 decrease of e-GFR. Using ROC curve, neopterin was accurately detect reduced kidney function defined as e-GFR of 60 ml/mnt or less (AUC = 0.88; 95%CI 0.74 to 1.00; SE = 0.07; p = 0.02). Using 7.46 ng/ml as cut-off value for normal neopterin concentrations, it was showed that sensitivity and specificity were 100% and 72% to detect the presence of reduced kidney function, consecutively. Neopterin may be used as a novel biomarker for reduced kidney function, for its role in the pathogenesis of cardiorenal syndrome in general population.
Keywords: neopterin, reduced kidney function, general population, biomarker cardiorenal syndrome